Linguistic nature of reality in Richard Rorty - Isa Mousazadeh; Muhammad Asghari; Mohammadreza Abdollahnejat (Pizhūhish/hā-yi Falsafī- Kalāmī, 2021)
In this article, our aim is to examine the place of “reality” in Richard Rorty’s thought in view of the important and key discussion of language in the philosophy of this thinker. In other words, we know that with the occurrence of the “linguistic turn” in the middle of the twentieth century, the relationship between language and reality has become one of the central debates of philosophy, especially analytical philosophy, and has become of particular importance. Is it language that determines the external reality for us? Is knowing the world outside the mind possible only through the possibilities that language gives us? And to what extent does the structure of language affect our cognitive pattern? These are only a part of the linguistic concerns that have occupied the minds of contemporary philosophers. The main concern and problem of the present article, which has been approached using a descriptive-analytical method, is to examine the relationship between language and reality in Richard Rorty’s thought and to show how he defends the linguistic structure of having reality. Rorty, following an analytical philosophy that, in addition to detailed analyses of traditional philosophical concepts, like the concepts of truth, meaning, necessity, etc. and by changing the discussion from experience to discussion from language in the direction of pragmatizing the basic principles of positivism, believes that it is trans-lingual (outside our descriptions) and trans-temporal (fixed and unchangeable). The common denominator that Plato found in the outside world and transferred to man in the Cartesian-Kantian tradition is sought in analytic philosophy in language, and so analytic philosophers continue to pursue the traditional philosophy project of providing a trans-historical and eternal framework for the accurate representation of the world. Rorty tries to overcome this view of analytical philosophers with a Darwinist and pragmatic view of language and under the influence of philosophers such as Wittgenstein.For Darwinists, language is a tool among other tools that gives its users the ability to better and more efficiently adapt to their environment and meet their needs. For the likes of Wittgenstein and like-minded people, despite their many and sometimes profound differences, language had an important and pivotal place with its eventual and possibility feature. Influenced by thinkers such as Wittgenstein, and in the context of his Darwinist and pragmatic approach to language, Rorty attributes certain characteristics to language that can be said to influence his whole thought. Firstly, he considers language as a tool like other tools and, therefore, considers it to have no fixed nature and identity. Given that it is not possible to leave the language and on the other hand language has a poetic and metaphorical character, the function of language cannot be a representation of reality and reality can never be available to us naked and as independent of language and descriptions. Therefore, from Rorty’s point of view, reality is a linguistic and constructed matter of language that we humans have invented in cooperation with each other and in accordance with our historical-cultural situation and needs. Of course, Rorty’s point in saying that reality is made by language is by no means that we create reality arbitrarily and as we wish; rather, what is happening is that we are responding to an external stimulus, a response of various sentence types that manifests itself as linguistic reactions.